LEAN MANUFACTURING SYSTEM KANBAN, ONE PIECE FLOW AND U TYPE OF POSITIONING SYSTEMS - Arzu ŞEKER (Fırat University, 2019)
In the global economy competition, managements have to present good quality products and service to make the customers happy, they must supply the consumers products with low price, good quality, fast delivering and also they should answer their changable demands with the variety of more products. It is imposible to supply the consumers with small amounts and few kinds of products in markets, on the contrary, it is necessary to improve marketing position with special products with low price for consumers. Lean Manufacturing, increasing the